2011
DOI: 10.1007/s11284-011-0886-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mud fiddler crabs (Uca pugnax) on the recruitment of halophyte seedlings in salt marsh dieback areas of Cape Cod (Massachusetts, USA)

Abstract: The effects of bioturbation by the mud fiddler crab (Uca pugnax) on salt marsh seedling recruitment were investigated experimentally in this study. Burrowing and foraging activity caused a large amount of soil disturbance, which in turn negatively impacted the establishment of seedlings. Either seeds did not germinate or seedlings were uprooted or buried. Although the majority of the published literature suggests a positive influence of Uca spp. on salt marsh plant growth, at high densities they have the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Impacts by consumers on plants are common across all ecosystems (Bigger and Marvier 1998), and are increasingly recognized for coastal habitats (He and Silliman 2016). There have been many studies in the past decade identifying the potential for strong negative effects of crabs on salt marshes (e.g., Holdredge et al 2009, Smith and Tyrrell 2012, Wilson et al 2012, Bertness et al 2014, Alberti et al 2015. So one goal FIG.…”
Section: Relationship Between Crabs and Marsh Integrity At Different mentioning
confidence: 99%
See 2 more Smart Citations
“…Impacts by consumers on plants are common across all ecosystems (Bigger and Marvier 1998), and are increasingly recognized for coastal habitats (He and Silliman 2016). There have been many studies in the past decade identifying the potential for strong negative effects of crabs on salt marshes (e.g., Holdredge et al 2009, Smith and Tyrrell 2012, Wilson et al 2012, Bertness et al 2014, Alberti et al 2015. So one goal FIG.…”
Section: Relationship Between Crabs and Marsh Integrity At Different mentioning
confidence: 99%
“…Tidal inundation strongly affects marsh distribution, so historically, academic and management emphasis has been placed on physical factors, such as sediment supply and marsh elevation, and how both can affect resilience to sea-level rise, another critical physical stressor (Kirwan and Murray 2007). In particular, herbivory and bioturbation by crabs can exert strong negative effects on marshes (e.g., Holdredge et al 2009, Smith and Tyrrell 2012, Bertness et al 2014, Alberti et al 2015. In particular, herbivory and bioturbation by crabs can exert strong negative effects on marshes (e.g., Holdredge et al 2009, Smith and Tyrrell 2012, Bertness et al 2014, Alberti et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). Any range shift in this species has ecosystem-wide consequences: deposit feeding and burrowing by U. pugnax impact infaunal species densities (Hoffman et al 1984), plant growth (Bertness 1985, Smith & Tyrrell 2012, Gittman & Keller 2013, decomposition rates (Thomas & Blum 2010), and sediment accumulation or erosion, depending on site-specific characteristics (Katz 1980, Smith & Green 2015. Also, burrow excavation is an activity that has been found to enhance carbon flux in other systems with burrowing semi-terrestrial crabs (PĂŒlmanns et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have investigated the effects of these sediment-filtering algivore and detritivore fiddler crabs on salt marsh plants and ecosystem functions thus far yield an ambivalent and possibly context-dependent picture. Some studies reported positive effects on cordgrass biomass that were attributed to crab-induced nutrient enrichment and/or soil oxygenation (Bertness 1985; Holdredge and others 2010), whereas others report negative effects on cordgrass seedling recruitment in sites where cordgrass has died back, and on marsh organic matter accumu-lation due to crab bioturbation (Thomas and Blum 2010;Smith and Tyrrell 2012). To date, however, it is unknown to what extent crabs interact with the cordgrass-mussel mutualism.…”
Section: Introductionmentioning
confidence: 99%